Behavioral factors to include in guidelines for lifelong oral healthiness: an observational study in Japanese adults - Shimozato Miho; Hayashi Matsumi; Toyama Atsushi; Nakagaki Haruo; Morita Ichizo; Watanabe Tsuyoshi; Tohmatsu Shimpei; Igo Junko; Sheiham Aubrey (BMC, 2006)
Abstract Background The aim of this study was to determine which behavioral factors to include in guidelines for the Japanese public to achieve an acceptable level of oral healthiness. The objective was to determine the relationship between oral health related behaviors and symptoms related to oral disease and tooth loss in a Japanese adult community. Methods Oral health status and lifestyle were investigated in 777 people aged 20 years and older (390 men and 387 women). Subjects were asked to complete a postal questionnaire concerning past diet and lifestyle. The completed questionnaires were collected when they had health examinations. The 15 questions included their preference for sweets, how many between-meal snacks they usually had per day, smoking and drinking habits, presence of oral symptoms, and attitudes towards dental visits. Participants were asked about their behaviors at different stages of their life. The oral health examinations included examination of the oral cavity and teeth performed by dentists using WHO criteria. Odds ratios were calculated for all subjects, all 10 year age groups, and for subjects 30 years or older, 40 years or older, 50 years or older, and 60 years or older. Results Frequency of tooth brushing (OR = 3.98), having your own toothbrush (OR = 2.11), smoking (OR = 2.71) and bleeding gums (OR = 2.03) were significantly associated with number of retained teeth in males. Frequency of between-meal snacks was strongly associated with number of retained teeth in females (OR = 4.67). Having some hobbies (OR = 2.97), having a family dentist (OR = 2.34) and consulting a dentist as soon as symptoms occurred (OR = 1.74) were significantly associated with number of retained teeth in females. Factors that were significantly associated with tooth loss in both males and females included alcohol consumption (OR = 11.96, males, OR = 3.83, females), swollen gums (OR = 1.93, males, OR = 3.04, females) and toothache (OR = 3.39, males, OR = 3.52, females). Conclusion Behavioral factors that were associated with tooth retention were frequency of eating snacks between meals, tooth brushing frequency, having one's own toothbrush, smoking and drinking habits, having hobbies, having a family dentist and when they had dental treatment. Clinical factors included bleeding gums, swollen gums, and toothache.